Komunikasi Eksternal Public Relations ‘Generation Girl’ dalam Mempromosikan Program-Program Organisasi - Marcha, Anandia Regina; Wijaya, Lina Sinatra (Jurnal Pustaka Komunikasi, 2024)
STEM (science, technology, engineering, and math) is a field of science and technology that is more popular with men than women. There is still a perception that women are not required to pursue higher education, particularly in STEM fields. From this perspective, “Generation Girl” aims to change these prejudices and encourage Indonesian women to study science in the STEM world through its programs. In order to attract the attention and interest of the target audience, “Generation Girl” will implement appropriate external public relations communication to attract Indonesian women to participate in “Generation Girl” programs. “Generation Girl” is a non-profit organization dedicated to educating women in STEM fields through innovative and exciting programs This study aims to describe the external communication strategies that have been carried out by “Generation Girl” to promote their programs in the community. This study used descriptive qualitative research. Data collection techniques used include interviews, observation, and documentation. The results of this study show that “Generation Girl” uses three media in disseminating information about its programs and organizations: online media, mass media, and non-mass media using external communication strategy theory. This makes it easier for the organization to recruit “Generation Girl” program participants.